Lithium ion battery negative electrode material and preparation method and application thereof
By using lithium-ion battery negative electrode materials with phosphorus-doped silene and carbon material layers in lithium-ion batteries, the problem of volume expansion of silicon-based materials during charging and discharging is solved, and the cycle stability and fast charging performance of the battery are improved. , enhances conductivity.
Patent Information
- Application Number
- CN202411152263.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-21
- Publication Date
- 2025-01-14
AI Technical Summary
The silicon-based negative electrode material in lithium-ion batteries will experience severe volume expansion during the charging and discharging process, resulting in the problems of capacity attenuation, increased internal resistance and poor conductivity.
Using phosphorus-doped silene as the matrix, and a phosphorus-doped carbon material layer is provided on its surface. The lithium-ion battery negative electrode material with a stable carbon material layer is prepared through mechanical fusion process, and the battery capacity and speed are improved by phosphorus doping. The charging capacity is to form a stable SEI film, enhance conductivity and prevent side reactions.
It effectively alleviates the problem of volume expansion during the charge and discharge cycle, improves the cycle stability and fast charging performance of the battery, enhances the conductivity, and extends the service life of the battery.
Smart Images

Figure BDA0005003969410000111 
Figure BDA0005003969410000121
Abstract
Description
Technical Field
[0001] The present invention relates to the field of batteries, and in particular to a negative electrode material for lithium-ion batteries and a preparation method and application thereof. Background Art
[0002] The research focus of negative electrode materials for lithium-ion batteries is developing towards high specific energy, high charge and discharge efficiency, high cycle performance and high rate charge and discharge resistance power battery materials. Silicene has many novel quantum effects similar to graphene, and silicene also has some advantages that graphene does not have, such as high transparency and high strength. However, silicon-based negative electrode materials will experience severe volume expansion during the charge and discharge process, causing capacity decay, consuming lithium ions and electrolyte, resulting in increased battery internal resistance and capacity decay, and poor conductivity.
[0003] In view of this, the present invention is proposed. Summary of the invention
[0004] The purpose of the present invention is to provide a lithium-ion battery negative electrode material and a preparation method and application thereof. The lithium-ion battery negative electrode material has the advantages of good cycle stability, excellent fast charging performance, etc.
[0005] In order to achieve the above-mentioned purpose of the present invention, the following technical solutions are particularly adopted:
[0006] One aspect of the present invention also relates to a negative electrode material for a lithium ion battery, comprising a substrate and a carbon material layer arranged on the surface of the substrate:
[0007] Wherein, the matrix comprises: phosphorus-doped silicon;
[0008] The carbon material layer includes phosphorus-doped silicene and carbon material coated on the phosphorus-doped silicene.
[0009] The lithium-ion battery negative electrode material is helpful to alleviate the volume expansion problem during the charge and discharge cycle, and phosphorus doping can increase the battery capacity.
[0010] Another aspect of the present invention also relates to a method for preparing the negative electrode material for a lithium ion battery, comprising the following steps:
[0011] (a) subjecting a mixture containing a phosphorus source, silicene and a carbon source to a first rotation treatment and a second rotation treatment to obtain a first mixed material;
[0012] (b) heating and carbonizing the first mixed material to obtain the negative electrode material for a lithium-ion battery.
[0013] The method for preparing the negative electrode material for a lithium-ion battery is simple and can obtain a negative electrode material with good cycle stability and strong fast charging capability by mechanical fusion.
[0014] Another aspect of the present invention also relates to a negative electrode plate, comprising the above-mentioned negative electrode material for a lithium-ion battery or the negative electrode material for a lithium-ion battery prepared by the above-mentioned method for preparing the negative electrode material for a lithium-ion battery.
[0015] Another aspect of the present invention also relates to a secondary battery, comprising the negative electrode plate.
[0016] Compared with the prior art, the present invention has the following beneficial effects:
[0017] (1) The lithium-ion battery negative electrode material provided by the present invention has a carbon material layer disposed on the surface of a silicene substrate, and both the substrate and the carbon material layer are doped with phosphorus. The layered structure of silicene is beneficial to alleviating the volume expansion problem during the charge and discharge cycle, and phosphorus doped in the substrate and the carbon material layer is beneficial to improving the battery capacity and fast charging capability.
[0018] (2) The preparation method of the negative electrode material for lithium ion batteries provided by the present invention utilizes a carbon source with a high softening point as a precursor of the carbon material layer, and introduces the carbon source into the surface of the silicene matrix by mechanical fusion. The introduced carbon source can be easily converted into a stable carbon material layer through a stabilization and carbonization process. The carbon material is doped with phosphorus to form a carbon material layer. The volume expansion of the carbon material layer during the lithiation / delithiation process forms a more stable and dense SEI film, enhances conductivity and prevents direct contact with the electrolyte to avoid side reactions.
[0019] (3) The preparation method of the negative electrode material of lithium ion battery provided by the present invention, after carbonization, the phosphorus functional groups remaining between different carbon layers can form PC bonds to increase the cross-linking of carbon layers, thereby increasing the mechanical strength of the carbon matrix to adapt to the change of Si volume and maintain the integrity of the matrix under stress. In addition, the larger phosphorus-containing functional groups will distort the carbon layer structure, form defects, increase the interlayer spacing, thereby providing more diffusion paths, reducing the surface activation energy, and improving the reaction kinetics of lithium ions. DETAILED DESCRIPTION
[0020] The technical scheme of the present invention will be clearly and completely described below in conjunction with specific embodiments, but it will be appreciated by those skilled in the art that the following described embodiments are part of embodiments of the present invention, rather than all embodiments, and are only used to illustrate the present invention, and should not be considered as limiting the scope of the present invention. Based on the embodiments in the present invention, all other embodiments obtained by those of ordinary skill in the art without making creative work, all belong to the scope of protection of the present invention. If specific conditions are not indicated in the embodiments, they are carried out according to normal conditions or conditions recommended by the manufacturer. If the manufacturer is not indicated in the reagents or instruments used, they are all conventional products that can be purchased commercially.
[0021] One aspect of the present invention also relates to a negative electrode material for a lithium ion battery, comprising a substrate and a carbon material layer arranged on the surface of the substrate:
[0022] Wherein, the matrix comprises: phosphorus-doped silicon;
[0023] The carbon material layer includes phosphorus-doped silicene and carbon material coated on the phosphorus-doped silicene.
[0024] The lithium-ion battery negative electrode material is provided with a carbon material layer on the surface of a silicene substrate, and both the substrate and the carbon material layer are doped with phosphorus. The layered structure of silicene is conducive to alleviating the volume expansion problem during the charge and discharge cycle, and phosphorus doped in the substrate and the carbon material layer is conducive to improving the battery capacity and fast charging capability.
[0025] Silicene has a nanoscale mesoporous structure. Phosphorus is embedded in the mesoporous structure of silicene to form phosphorus-doped silicene. A small amount of phosphorus atoms replace some silicon atoms. Four of the outer electrons of the phosphorus atoms form covalent bonds with silicon. This creates a free-moving electron, which increases the electrical conductivity of the silicene material and enhances the fast charging ability of silicene as a negative electrode material.
[0026] Phosphorus doping in carbon materials is beneficial to increase the mechanical strength of the carbon matrix to adapt to the change in silicon volume, improve the cycle stability of the negative electrode material, provide more diffusion paths for lithium ions, and increase the reaction kinetics of lithium ions.
[0027] Further, the thickness of the carbon material layer is 10-20 nm, including but not limited to any point value of 10 nm, 12 nm, 14 nm, 16 nm, 18 nm or 20 nm or a range value between any two thereof. Increasing the thickness of the carbon material layer will improve the conductivity, but if the carbon material layer is too thick, the gram capacity and capacity retention rate will be reduced.
[0028] Furthermore, in the matrix, the doping ratio of silicene and phosphorus is 100:(5-10), including but not limited to 100:5, 100:6, 100:7, 100:8, 100:9 or 100:10. The doping ratio of silicene and phosphorus is limited to a reasonable range, which can improve the conductivity of the negative electrode material and improve the fast charging performance of the negative electrode material. Phosphorus can enhance the mechanical strength of the matrix, increase the interlayer spacing, and improve the fast charging capability. Too much phosphorus will reduce the conductivity.
[0029] Furthermore, in the carbon material layer, the doping ratio of silicene, carbon material and phosphorus is 100:10 to 13:5 to 10. The doping ratio of carbon material and phosphorus is limited within a reasonable range, which can improve the cycle stability of the negative electrode material and provide more diffusion paths for lithium ions.
[0030] Furthermore, phosphorus is doped on the surface of the silicene. Silicene is a layered silicon material with a honeycomb structure, and the surface of silicene involved in the present invention includes both the inner surface of silicene and the inner surface of silicene.
[0031] Another aspect of the present invention also relates to a method for preparing the negative electrode material for a lithium ion battery, comprising the following steps:
[0032] (a) subjecting a mixture containing a phosphorus source, silicene and a carbon source to a first rotation treatment and a second rotation treatment to obtain a first mixed material;
[0033] (b) heating and carbonizing the first mixed material to obtain the negative electrode material for a lithium-ion battery.
[0034] The method for preparing the negative electrode material of a lithium-ion battery uses a carbon source with a high softening point as a precursor of a carbon material layer, and introduces the carbon source into the surface of a silicene matrix by mechanical fusion. The introduced carbon source can be easily converted into a stable carbon material layer through a stabilization and carbonization process. The carbon material is doped with phosphorus to form a carbon material layer. The volume expansion of the carbon material layer during the lithiation / delithiation process forms a more stable and dense SEI film, enhances conductivity, and prevents direct contact with the electrolyte to avoid side reactions.
[0035] In the preparation method of the negative electrode material for lithium-ion batteries, after carbonization, the phosphorus functional groups remaining between different carbon layers can form PC bonds to increase the cross-linking of the carbon layers, thereby increasing the mechanical strength of the carbon matrix to adapt to the change in Si volume and maintain the integrity of the matrix under stress. In addition, larger phosphorus-containing functional groups will distort the carbon layer structure, form defects, increase the interlayer spacing, thereby providing more diffusion paths, reducing the surface activation energy, and increasing the reaction power of lithium ions.
[0036] During the carbonization process, the carbon precursor on the surface of the phospho-silicene composite material cokes to form a phospho-silicene composite material coating layer. The carbon layer effectively reduces the structural defects such as cracks and pulverization caused by the volume expansion and contraction of silicene during the charge and discharge process. In addition, it also reduces the contact resistance between active materials, promotes the rapid movement of electrons, and provides an effective path for electrons.
[0037] Further, the mass ratio of the phosphorus source, the silicene and the carbon source is 90:225-1800:25-200, including but not limited to 90:225:200, 90:300:190, 90:400:190, 90:500:180, 90:600:170, 90:700:160, 90:800:150, 90:900:140, 90:1000:130, 90:1100:120, 90:1200:110, 90:1300:100, 90:1400:90, 90:1500:80, 90:1600:60, 90:1700:40, or 90:1800:25.
[0038] Furthermore, the phosphorus source includes but is not limited to: phosphoric acid and / or phosphobenzoic acid.
[0039] Further, the structural formula of phosphobenzoic acid is:
[0040] Furthermore, the carbon source includes but is not limited to: asphalt and / or phenolic resin.
[0041] Asphalt with a high softening point is used as a carbon precursor. The high softening point and good temperature stability are conducive to the formation of a stable carbon layer. During the carbonization process, a stable phosphorus-doped carbon layer is formed on the surface of silicene. The carbon layer can enhance conductivity, prevent direct contact with the electrolyte, and inhibit side reactions with the electrolyte. Asphalt is used as a carbon precursor, the asphalt ash content is 0.04%, and the fixed carbon content is 72.1%.
[0042] Further, the speed of the first rotation process is 2100-2300 rpm, including but not limited to any point value of 2100 rpm, 2150 rpm, 2200 rpm, 2250 rpm or 2300 rpm or a range value between any two of them.
[0043] Furthermore, the time of the first rotation processing is 25 to 35 minutes, including but not limited to any one of 25 minutes, 27 minutes, 29 minutes, 31 minutes, 33 minutes or 35 minutes, or a range between any two of them.
[0044] The first rotation process helps to evenly disperse the material and avoid agglomeration.
[0045] Further, the speed of the second rotation process is 4400-4600 rpm, including but not limited to any point value of 4400 rpm, 4450 rpm, 4500 rpm, 4550 rpm or 4600 rpm or a range value between any two of them.
[0046] Furthermore, the second rotation process is performed for 10 to 20 minutes, including but not limited to any one of 10 minutes, 12 minutes, 14 minutes, 16 minutes, 18 minutes or 20 minutes, or a range between any two of them.
[0047] The second rotation process can break up large particles and facilitate rapid fusion of materials.
[0048] Furthermore, the temperature of the heating treatment is 280-320° C., including but not limited to any point value of 280° C., 290° C., 300° C., 310° C. or 320° C. or a range of values between any two of them. The heating treatment pre-oxidizes the carbon source to improve the thermal stability of the carbon material.
[0049] Furthermore, the heating treatment time is 14 to 18 hours, including but not limited to any one of 14 hours, 15 hours, 16 hours, 17 hours or 18 hours or a range between any two of them.
[0050] Furthermore, the heating rate of the heat treatment is 3 to 7°C / min, including but not limited to any point value of 3°C / min, 4°C / min, 5°C / min, 6°C / min or 7°C / min or a range value between any two of them.
[0051] Furthermore, the carbonization temperature is 820-880°C, including but not limited to any point value of 820°C, 830°C, 840°C, 850°C, 860°C, 870°C or 880°C or a range value between any two of them. The carbonization temperature is controlled within a certain range, and the interlayer spacing with a higher degree of disorder is larger, which is beneficial to improving the capacity and performance of the battery. As the temperature increases, the interlayer spacing decreases and the capacity decreases.
[0052] Furthermore, the carbonization time is 1 to 3 hours, including but not limited to any one of 1 hour, 1.5 hours, 2 hours, 2.5 hours or 3 hours or a range between any two of them.
[0053] Furthermore, the heating rate of the carbonization is 3-7°C / min, including but not limited to any one of 3°C / min, 5°C / min, 6°C / min or 7°C / min or a range between any two of them.
[0054] Further, the heating treatment and carbonization are performed under an inert atmosphere.
[0055] Another aspect of the present invention also relates to a negative electrode plate, comprising the above-mentioned negative electrode material for a lithium-ion battery or the negative electrode material for a lithium-ion battery prepared by the above-mentioned method for preparing the negative electrode material for a lithium-ion battery.
[0056] Another aspect of the present invention also relates to a secondary battery, comprising the negative electrode plate.
[0057] The embodiments of the present invention will be described in detail below in conjunction with the examples, but it will be appreciated by those skilled in the art that the following examples are only used to illustrate the present invention and should not be considered as limiting the scope of the present invention. If no specific conditions are specified in the examples, the conditions are carried out according to normal conditions or the conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be obtained commercially.
[0058] Example 1
[0059] The method for preparing the negative electrode material of a lithium ion battery provided in this embodiment comprises the following steps:
[0060] (1) solid phosphoric acid, silicene and asphalt are placed in a container at a mass ratio of 90:1800:200, and a mixing / dispersion process is performed by a rotating device. In a mechanical melting process, the initial dry coating process is performed at 2200 rpm for 30 minutes and then at 4500 rpm for 15 minutes;
[0061] (2) The mixture was placed in a furnace and stabilized at 300 °C for 16 h with a heating rate of 5 °C / h in a nitrogen atmosphere; then, carbonization was performed at 850 °C with a heating rate of 5 °C / min for 2 h.
[0062] Example 2
[0063] The method for preparing the negative electrode material for a lithium-ion battery provided in this embodiment is different from that in Embodiment 1 only in that solid phosphoric acid, silicene, and asphalt are placed in a container at a mass ratio of 90:900:100.
[0064] Example 3
[0065] The method for preparing the negative electrode material for a lithium-ion battery provided in this embodiment is different from that in Embodiment 1 only in that solid phosphoric acid, silicene, and asphalt are placed in a container in a mass ratio of 90:450:50.
[0066] Example 4
[0067] The method for preparing the negative electrode material for a lithium-ion battery provided in this embodiment is different from that in Embodiment 1 only in that solid phosphoric acid, silicene, and asphalt are placed in a container at a mass ratio of 90:225:25.
[0068] Example 5
[0069] The preparation method of the negative electrode material for a lithium-ion battery provided in this embodiment is different from that in Embodiment 1 only in step 2, carbonization is performed at 600° C. at a heating rate of 5° C. / min for 4 h.
[0070] Example 6
[0071] The difference between this embodiment and embodiment 1 is that the carbon source is phenolic resin.
[0072] Example 7
[0073] The difference between this embodiment and embodiment 1 is that the phosphorus source is phosphobenzoic acid.
[0074] Example 8
[0075] The method for preparing the negative electrode material of a lithium ion battery provided in this embodiment comprises the following steps:
[0076] (1) under inert gas protection, solid phosphoric acid powder and silicene are mixed in a mass ratio of 1:20, and the reactor is heated to 600° C. at a heating rate of 1° C. / min;
[0077] (2) placing the phosphosilicene composite material and asphalt in a container and performing a mixing / dispersion process by a rotating device. In the mechanical melting process, the initial dry coating process is performed at 2200 rpm for 30 min and then at 4500 rpm for 15 min;
[0078] (3) The phosphosilicene composite material-asphalt composite material was placed in a furnace and stabilized at 300 °C for 16 h with a heating rate of 5 °C / h in a nitrogen atmosphere. Then, it was carbonized at 850 °C for 2 h with a heating rate of 5 °C / min.
[0079] Example 9
[0080] The method for preparing the negative electrode material of a lithium ion battery provided in this embodiment comprises the following steps:
[0081] (1) solid phosphoric acid, silicene and asphalt are placed in a container at a mass ratio of 90:1000:100, and a mixing / dispersion process is performed by a rotating device. In a mechanical melting process, the initial dry coating process is performed at 2100 rpm for 35 min and then at 4400 rpm for 20 min;
[0082] (2) The mixture was placed in a furnace and stabilized at 320 °C for 14 h with a heating rate of 7 °C / h in a nitrogen atmosphere; then, carbonization was performed at 820 °C with a heating rate of 3 °C / min for 3 h.
[0083] Example 10
[0084] The method for preparing the negative electrode material of a lithium ion battery provided in this embodiment comprises the following steps:
[0085] (1) solid phosphoric acid, silicene and asphalt were placed in a container at a mass ratio of 90:1500:160, and a mixing / dispersion process was performed by a rotating device. In the mechanical melting process, the initial dry coating process was performed at 2300 rpm for 25 min and then at 4600 rpm for 10 min;
[0086] (2) The mixture was placed in a furnace and stabilized at 280 °C for 18 h with a heating rate of 3 °C / h in a nitrogen atmosphere; then, carbonization was performed at 880 °C with a heating rate of 7 °C / min for 1 h.
[0087] Embodiment 11
[0088] The only difference between this embodiment and embodiment 1 is that the initial dry coating process is performed at 1900 rpm for 30 min.
[0089] Example 12
[0090] The only difference between this embodiment and embodiment 1 is that the initial dry coating process is performed at 2200 rpm for 30 minutes and then at 4800 rpm for 15 minutes.
[0091] Embodiment 13
[0092] The only difference between this embodiment and embodiment 1 is that the stabilization process is carried out at 350° C. for 16 h.
[0093] Embodiment 14
[0094] The only difference between this embodiment and embodiment 1 is that the carbonization temperature is 900°C.
[0095] Comparative Example 1
[0096] The method for preparing the negative electrode material of a lithium ion battery provided in this comparative example comprises the following steps:
[0097] (1) placing silicene and asphalt in a container at a mass ratio of 1800:200 and performing a mixing / dispersion process by a rotating device, in a mechanical melting process, the initial dry coating process is performed at 2200 rpm for 30 min and then at 4500 rpm for 15 min;
[0098] (2) Same as Example 1.
[0099] Comparative Example 2
[0100] The method for preparing the negative electrode material of a lithium ion battery provided in this comparative example comprises the following steps:
[0101] (1) solid phosphoric acid and silicene are placed in a container at a mass ratio of 1:20 and mixed / dispersed by a rotating device. In a mechanical melting process, the initial dry coating process is performed at 2200 rpm for 30 min and then at 4500 rpm for 15 min;
[0102] (2) Same as Example 1.
[0103] Comparative Example 3
[0104] The method for preparing the negative electrode material for a lithium-ion battery provided in this comparative example is different from that in Example 1 only in that silicene is replaced by micron silicon.
[0105] Experimental example
[0106] The negative electrode was prepared from a coating slurry of negative electrode material, carbon black (super-P), carboxymethyl cellulose (CMC) and styrene-butadiene rubber (SBR) in a mass ratio of 94.5:1.5:2.5:1.5. The slurry was evenly pasted on a 6μm copper foil using a scraper and dried in a vacuum oven at 80°C for 12 hours. The working electrode diameter was 14.0 mm, and the loading mass of the active material was about 1.5 mg / cm 2 1.0M LiPF6 electrolyte was dissolved in EC and DEC with a volume ratio of 1:1. Metal lithium sheet was used as the positive electrode, Celgard2400 separator was used, and button cells were assembled for electrochemical testing in an argon atmosphere in a glove box.
[0107] The assembled button cell was evaluated using a multi-channel battery cycler to test its electrochemical performance. The test method was to perform a charge and discharge test at room temperature (25°C) with a 0.05C DC discharge cutoff voltage of 0.005V, a 0.005V constant voltage discharge cutoff current of 50μA, and a 0.1C charge cutoff voltage of 2V. The test data is shown in Table 1.
[0108] Table 1
[0109]
[0110]
[0111] It can be seen from Table 1 that different mass ratios of phosphorus source and carbon source, dispersion and stabilization process of materials will affect capacity and cycle performance. Example 1 has higher gram capacity and cycle retention rate, and better cycle stability. It can be seen from the comparative example that phosphorus source or carbon source will increase gram capacity and cycle performance.
[0112] Although the present invention has been illustrated and described with specific embodiments, it should be appreciated that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Those skilled in the art should understand that the technical solutions described in the above embodiments may be modified, or some or all of the technical features thereof may be replaced by equivalents without departing from the spirit and scope of the present invention. However, these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present invention. Therefore, this means that all such replacements and modifications within the scope of the present invention are included in the appended claims.
Claims
1. A negative electrode material for a lithium ion battery, characterized in that: It includes a substrate and a carbon material layer arranged on the surface of the substrate: Wherein, the matrix comprises: phosphorus-doped silicon; The carbon material layer includes phosphorus-doped silicene and carbon material coated on the phosphorus-doped silicene.
2. The negative electrode material for lithium-ion batteries according to claim 1, characterized in that: Includes at least one of the following technical features: (1) The thickness of the carbon material layer is 10 to 20 nm; (2) In the matrix, the mass ratio of silicene to phosphorus is 100:(5-10); (3) In the carbon material layer, the mass ratio of silicene, carbon material and phosphorus is 100:10-13:5-10; (4) Phosphorus is doped on the surface of the silicene.
3. The method for preparing a negative electrode material for a lithium ion battery according to claim 1 or 2, characterized in that: The following steps are involved: (a) subjecting a mixture containing a phosphorus source, silicene and a carbon source to a first rotation treatment and a second rotation treatment to obtain a first mixed material; (b) heating and carbonizing the first mixed material to obtain the negative electrode material for a lithium-ion battery.
4. The method for preparing a negative electrode material for a lithium ion battery according to claim 3, characterized in that: Includes at least one of the following technical features: (1) The mass ratio of the phosphorus source, the silicene and the carbon source is 90:225-1800:25-200; (2) The phosphorus source includes: phosphoric acid and / or phosphobenzoic acid; (3) The carbon source includes: asphalt and / or phenolic resin.
5. The method for preparing a negative electrode material for a lithium ion battery according to claim 3, characterized in that: The speed of the first rotation treatment is 2100-2300 rpm; And / or, the first rotation treatment time is 25 to 35 minutes.
6. The method for preparing a negative electrode material for a lithium ion battery according to claim 3, characterized in that: The speed of the second rotation process is 4400-4600 rpm; And / or, the second rotation treatment is performed for 10 to 20 minutes.
7. The method for preparing a negative electrode material for a lithium ion battery according to claim 3, characterized in that: Includes at least one of the following technical features: (1) The temperature of the heating treatment is 280-320° C.; (2) The heating treatment time is 14 to 18 hours; (3) The heating rate of the heating treatment is 3 to 7°C / min.
8. The method for preparing a negative electrode material for a lithium ion battery according to claim 3, characterized in that: Includes at least one of the following technical features: (1) The carbonization temperature is 820-880° C.; (2) The carbonization time is 1 to 3 hours; (3) The heating rate of the carbonization is 3 to 7°C / min.
9. A negative electrode plate, characterized in that: The invention comprises a lithium ion battery negative electrode material according to claim 1 or 2 or a lithium ion battery negative electrode material prepared by the preparation method of the lithium ion battery negative electrode material according to any one of claims 3 to 8.
10. A secondary battery, characterized in that: Including the negative electrode sheet as described in claim 9.